Technical comment—Ten fundamental principles on defining and expressing thermal exposure as boundary conditions in fire safety engineering. (10th July 2018) - Wickström, Ulf; Hunt, Sean; Lattimer, Brian; Barnett, Jonathan; Beyler, Craig
Summary: Predicting the temperature of an exposed object or even a person is one of the most common tasks of fire safety engineering. However, the nonlinear nature of heat transfer and the challenge of changing material properties with temperature have plagued precise predictions. In addition, as methodologies are developed, one of the biggest challenges is to apply them to known scenarios where temperatures and heat fluxes have been measured. The interpretations of such measurements are, however, often clouded by the lack of common understanding of the reported values and how they shall be translated into boundary conditions to be used for calculations. This technical comment summarizes the Fundamental Principles that are crucial to properly identifying the fire exposure so that appropriate temperature predictions can be made.